Civil Life, Globalization, And Political Change in Asia : Organization between family and state (Routledge, 2005)
Academics and policy makers have grown increasingly interested in the ways that non-governmental organizations (NGOs) may encourage better governance, democratic politics, and perhaps ultimately a global civil society. In Civil Life, Globalization and Political Change in Asia, Robert Weller has brought together an international group of experts on the subject, whose chapters address these questions through a series of extensive case studies from East and Southeast Asia including Japan, China, South Korea, Taiwan, Hong Kong, Singapore, Indonesia and Vietnam.